EKSPLORASI BENTUK - BENTUK KETIDAK SOPANAN SISWA TERHADAP GURU: STUDI FENOMENOLOGI DI MADRASAH TSANAWIYAH AL MUNAWWARAH KOTA JAMBI - Lutfiana; Fadhil, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the increasing phenomenon of student disrespect toward teachers, which has the potential to disrupt the learning process, weaken pedagogical relationships, and erode character values in schools. This research aims to explore the forms of student disrespect toward teachers, analyze teachers’ and students’ perceptions of such behavior, and identify the psychological impacts experienced by teachers. The study employed a qualitative method with a phenomenological approach. The research was conducted at MTs Al-Munawwarah Kota Jambi, particularly in class IX B, and participants were selected through purposive sampling. Data were collected through participatory observation, semi-structured interviews, and documentation, and were analyzed inductively through data condensation, data display, and conclusion drawing, while data validity was ensured through source and method triangulation. The results show that student disrespect appears in verbal forms such as the use of harsh language and impolite interruptions, non-verbal forms such as dismissive facial expressions and unresponsive attitudes, and digital forms such as inappropriate posts or messages related to teachers on social media. The main contributing factors include family background, peer influence, and exposure to social media. The impacts experienced by teachers include emotional distress, feelings of being undervalued, decreased teaching motivation, and disruptions to classroom climate and learning effectiveness. This study concludes that student disrespect is a multidimensional problem that requires a comprehensive response through strengthening character education, internalizing religious and cultural values of politeness, and fostering active collaboration between schools and parents to build a sustainable culture of respect.